Dynamic GTS scheduling of periodic skippable slots in IEEE 802.15.4 Wireless Sensor Networks - Tiago Semprebom (2009)
The IEEE 802.15.4 standard offers a flexible communication solution for low-rate wireless small area networks. When the beacon mode is enabled, real-time communication is possible by using the Guaranteed Time Slots (GTS) mechanism. However, the beacon-enabled mode only supports a maximum of seven GTS allocated in each superframe, preventing other nodes to benefit from the guaranteed service. This paper introduces the SIGHT (Skips In GTS scHeduling for IEEE 802.15.4 neTworks) model, which incorporates a dynamic GTS allocation policy for IEEE 802.15.4 networks based on the (m,k)-firm task model. Our approach ensures that at least m messages are allocated in a guaranteed slot, for any k consecutive superframes. It adopts a deterministic schedulability test and an on-line prioritization heuristic algorithm called Slotted DBP (Distance Based Priority) to attend requests according to this schedulability model. A simulation model has been developed, in order to compare the behaviour in overload conditions of the proposed Slotted DBP with other approaches (DWCS and FIFO).